Investigating the Impact of Management Practices on the Work Productivity of Administrative Staff of Faryab University - Musammem, Pohaniar Yama (Integrated Journal for Research in Arts and Humanities, 2022)
Today, one of the most important and effective healthy communication between managers and work Kananin achieving goals as big as the mission and vision Faryab University Compliance with ethical and behavioral principles. Level Management to achieve goals University and Better use of expertise and management practices and human resources skills and Communication with different layers of work Kenan at Faryab University. It requires having skills in public relations and a certain personality sobriety’s, which only successful managers have. Based on the role of ethical standards in management at the level of Faryab University, providing mental comfort, reducing stress and encouraging employees in the work environment Important Faryab University Deemed to be. According to the findings of the research, the participatory management method has been used at the management levels in Faryab University, which has been a favorable result for raising the level of work quality. Still Determining the method Management Participating in management levels in Faryab University To improve the performance of employees with a focus Satisfaction Administrative staff, Cooperation and employee motivation Official The main objective To achieve the mission and vision of Faryab University. This research is practical in terms of classification based on the purpose, and in terms of classification based on the method, this research can be descriptive research – Correlation counts. The number of sample members according to all work Kanan Faryab University used the method of Morgan's table and it was obtained from a statistical population of fifty (50) people, of which 40 people were selected as a sample according to the table. The tool for collecting information is a questionnaire, to analyze the data from the software SPSS was used for descriptive and inferential statistics (correlation and correlation).